Demographic and clinical predictors of treatment outcomes in invasive lobular carcinoma breast cancer: insights from Cox regression analysis - Sonia Kaindal; B. Venkataramana (Discover Oncology)
Abstract Invasive lobular carcinoma (ILC) ranks as the second most prevalent type of breast cancer after invasive ductal carcinoma (IDC). Understanding the demographics, clinical, and treatment outcomes of patients with ILC is essential for developing personalized treatment strategies. The purpose of this study is to evaluate the risk factors, treatment efficacy, demographics, and effects of marital status on treatment approaches for patients with lobular carcinoma. The data retrieved from the SEER program included 2,085 patients with lobular carcinoma. Descriptive statistics describe their clinical and demographical characteristics, while inferential statistics, including the Pearson chi-square test and Cox regression models, assess treatment outcomes based on age and clinicopathological factors. Among the cohort, 7.9% of patients were aged 30–44, 40.1% were aged 45–59, and 52% were aged 60–74. The analysis indicated that patients aged 45–59 predominantly received radiation therapy, while those aged 60–74 primarily underwent chemotherapy. Compared to older individuals, younger patients demonstrated a more favorable response to chemotherapy (HR = 0.653, 95% CI: 0.261–1.633) and radiation therapy (HR = 0.625, 95% CI: 0.249–1.565). Age at diagnosis was an independent factor in breast cancer of lobular carcinoma. The Cox regression models revealed significant disparities in treatment effects across different age groups and clinicopathological characteristics. The chi-square analysis showed no significant associations for most variables, indicating that unmeasured factors influence chemotherapy and radiation therapy. A frailty model better captures risk factors, improving treatment decision-making and patient outcome analysis. This study emphasizes the need to evaluate demographic and clinical factors in treatment planning for lobular carcinoma patients. The findings suggest that personalized treatment strategies should be developed to address the varying responses to treatment among different patient cohorts.